Visual re-identification of individual objects: a core problem for organisms and AI - Fields, Chris (Cognitive processing, 2016)
Two open questions about the visual re-identification of individual objects over extended time periods are briefly reviewed: (1) How much a priori information about the nature of objects, identity and time is required to support robust individual object re-identification abilities? and (2) how do epistemic feelings, such as the feeling of familiarity, contribute both to object re-identification and to the perception of opportunities and risks associated with individual objects and their affordances? The ongoing interplay between experiments that can be carried out with human subjects and experiments made possible with robotic systems is examined. It is suggested that developmental robotics, including virtual-reality simulations of robot–environment interactions, may provide the best route to understanding both the implementation of epistemic feelings in humans and their functional contribution to the identification of persistent individual objects.